A Behavioral Theory of Sustainable Supply Chain Management Decision Making in Non‐exemplar Firms. Issue 1 (28th December 2015) - Kirchoff, Jon F.; Omar, Ayman; Fugate, Brian S.
Abstract : Empirical evidence shows that investments in sustainable supply chain management can improve economic‐based performance. Thus, based on standard economic theory, rational business decision makers should and will implement sustainable supply chain management practices. However, through inductive research methods, we uncovered an intriguing theme that runs counter to both the existing empirical evidence and such economic‐based assumptions. We find that managers operating in firms without exemplary sustainable supply chain management practices face immense hurdles in developing a business case for implementing sustainability initiatives. Despite the lack of such practices—and in tension with the prevailing empirical evidence and theory—the firms within which these managers operate were performing well on economic‐based performance metrics. Departing from the neoclassical economic theory of the firm, we apply the Behavioral Theory of the Firm's theoretical assumptions to findings which suggest four segments of managers in non‐exemplary firms who vary based primarily on how they perceive strategic vulnerability, evaluate choices, and utilize sustainability knowledge.